Lentivirus-Mediated RNA Interference Targeting the Long Noncoding RNA HOTAIR Inhibits Proliferation and Invasion of Endometrial Carcinoma Cells In Vitro and In Vivo. Issue 4 (1st May 2014) - Huang, Jiaming; Ke, Peiqi; Guo, Luyan; Wang, Wei; Tan, Hao; Liang, Yanchun; Yao, Shuzhong
Abstract : Objective: The overexpression of long noncoding RNA HOTAIR is associated with various aggressive solid carcinomas. However, its relationship with endometrial carcinoma has not been reported. The present study aimed to investigate the expression of the long noncoding RNA HOTAIR in endometrial carcinoma, its relationship with the carcinoma's clinicopathologic features, and the biological function of HOTAIR in regulating endometrial cancer cell proliferation and invasion in vitro and in vivo. Methods: The expression of HOTAIR was detected in different tissues and cell lines by real-time PCR. Lentivirus-mediated HOTAIR-specific shRNAvectors were transfected into endometrial cancer HEC-1A cells. Cell proliferation and colony formation were examined by CCK-8 assays and colony formation assays, respectively. Invasion and migration were examined by Transwell assays. Flow cytometry assay was used to examine the cell cycle. In addition, xenograft model assays were performed to analyze the growth of endometrial cancer cells in vivo. Results: Our data showed that HOTAIR expression was higher in endometrial cancer cells and tissues than in normal endometrial tissues. HOTAIR expression was closely related to the tumor stage ( P = 0.045), myometrial invasion ( P = 0.014), and lymph node metastasis ( P = 0.033). The down-regulation of HOTAIR resulted in a significant inhibition of cell proliferation, migration, and invasion and in cell cycle arrest at the G0/G1 phase. Furthermore, HOTAIR depletion significantly suppressed the endometrial cancer tumorigenesis in vivo. Conclusions: This study is the first to suggest that HOTAIR plays an important role in the carcinogenesis of endometrial cancer. Targeting HOTAIR may be a novel therapeutic strategy for endometrial cancer.